Pengabdian Masyarakat dalam Pengembangan UMKM Bakso Bu Mur: Pendampingan dan Pemberdayaan - Suprihandari, Miya Dewi; Emmywati, Emmywati; Sanggarwati, Diah Ayu; Komariah, Fitri; Sadiqin, Amin; Manape, Leonard Adrie (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, particularly in job creation and contributing to the Gross Domestic Product (GDP). One of the leading MSMEs in the culinary field is Bakso Bu Mur. However, it faces financial issues, limited digital marketing, and poor relations with the local community. A community service program conducted by STIE Mahardhika Surabaya aims to address these issues through training and assistance in business management, digital marketing, and community empowerment. This study employs a qualitative descriptive method with a case study approach to analyze the implementation and impact of the community service program on the development of Bakso Bu Mur MSME. Data were collected through in-depth interviews, observation, questionnaires, and documentation. The findings indicate that the program successfully enhanced financial management skills and operational efficiency at Bakso Bu Mur. Digital marketing training improved product visibility and sales through social media and e-commerce platforms. Additionally, local community empowerment strengthened the relationship between the MSME and the surrounding community, fostering a more sustainable business ecosystem. In conclusion, the community service program implemented by STIE Mahardhika Surabaya has had a significant positive impact on the development of Bakso Bu Mur MSME. This program demonstrates that collaboration between higher education institutions and MSMEs can benefit the local economy. This approach can be adopted to support culinary MSMEs across Indonesia.